2006
DOI: 10.3177/jnsv.52.297
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Natto, a Fermented Soybean Preparation, to Prevent Excessive Plasma Vitamin K Concentrations in Patients Taking Warfarin

Abstract: SummaryThe purpose of this study is to find a method of cooking natto that prevents the appearance of high-plasma vitamin K concentrations after the consumption of natto, so that patients taking warfarin can benefit from eating natto. Five cooking methods were examined to determine which could most effectively decrease the count of the living Bacillus subtilis in natto. Volunteers ate natto or treated natto, and their plasma vitamin K level was measured at 5, 8, 24 and 48 h thereafter. One gram of natto contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Subsequently, there has been some preliminary evidence of thrombolysis in rats Consequence of patient substitution of nattokinase for warfarin after aortic valve replacement with a mechanical prosthesis Maqsood M. Elahi, PhD, Charles H. Choi, BS, Subbareddy Konda, MD, and Jay G. Shake, MD (3,4) and evidence of complete dissolution of arterial thrombi within 5 hours of oral administration of nattokinase in dogs (5). However, the authors of this case report have found limited data on the anticoagulation properties of natto and nattokinase in human subjects (6)(7)(8). Th rombin activity has been found to be increased following thrombolysis, which in turn may have paradoxically increased our patient's risk of valve thrombosis (9,10).…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, there has been some preliminary evidence of thrombolysis in rats Consequence of patient substitution of nattokinase for warfarin after aortic valve replacement with a mechanical prosthesis Maqsood M. Elahi, PhD, Charles H. Choi, BS, Subbareddy Konda, MD, and Jay G. Shake, MD (3,4) and evidence of complete dissolution of arterial thrombi within 5 hours of oral administration of nattokinase in dogs (5). However, the authors of this case report have found limited data on the anticoagulation properties of natto and nattokinase in human subjects (6)(7)(8). Th rombin activity has been found to be increased following thrombolysis, which in turn may have paradoxically increased our patient's risk of valve thrombosis (9,10).…”
Section: Discussionmentioning
confidence: 94%
“…Although no controlled studies have been conducted to demonstrate natto's safety with regard to avoiding clot mobilization, historically, documentation records that natto is significantly safe. 160 NK requires to lower patient's doses of coumadin due to drug interaction. Physicians also need to monitor clotting time (PT, PTT, and INR) in the first weeks of natto or NK therapy until these levels are stable.…”
Section: Contraindications and Precautionsmentioning
confidence: 99%
“…Because NK is a very potent fibrinolytic agent, it is theoretically possible that regular use could break a clot loose from a lower‐extremity vein and cause a pulmonary embolism or pass upward to brain and cause a stroke. Although no controlled studies have been conducted to demonstrate natto's safety with regard to avoiding clot mobilization, historically, documentation records that natto is significantly safe …”
Section: Introductionmentioning
confidence: 99%
“…So, it is important to find a suitable cooking method for natto to decrease the content of bacilli, so that patients on warfarin can eat natto without encountering excessive plasma concentrations of vitamin K. Homma et al (2006) developed five cooking methods to decrease the number of Bacillus subtilis in natto. Thirty-two healthy volunteers (19 males and 13 females) aged from 21 to 60 years participated in the study.…”
Section: Intervention With Warfarinmentioning
confidence: 99%